Control and indicating equipment communicating via the peripheral component interconnect express bus - Vaclav Mach; Milan Adámek; Jan Valouch; Karla Barčová (Bulletin of Electrical Engineering and Informatics, 2020)
Nowadays, the Intruder Alarm system is commonly used to protect the life, health and the possession of people in big companies. However, these systems have limited options for managing and remote control. This lack is very often criticized by big companies which want to use the Intruder Alarm System with other applications like Access and Attendance control. The aim of this article is to design a Control and Indicating Equipment which can be implemented into commercially made Personal Computer as expansion card. The designed card provides the main function of the Intruder Alarm system which can be further extended by other applications. The system consists of external communication like Universal Serial Bus, Ethernet and General Packet Radio Service interface. Each individual part of the system is driven by a single microcontroller ATmega328P which can handle communication and evaluation of the current state obtained by devices connected to it. The design can offer all alarm and non-alarm visualization of smart control like irrigation, lights control, audio system, etc. The whole design is driven by the proper standardization and the design consists of every schematic which comes with the explanation